Development of Linear Motion Assessment Using Evidence-Centered Design - Hulu, Hepi Kharisda; Sirait*, Judyanto; Firdaus, Firdaus; Balta, Nuri (Universitas Syiah Kuala, 2025)
Linear motion is one of the basic concepts in physics, so an assessment that can measure students' abilities in this material is necessary. The assessments created by teachers tend to only evaluate students' abilities in formula calculations without measuring their understanding in depth. This research aims to develop assessments on the topic of linear motion using the evidence-centered design (ECD) framework. ECD is a framework that focuses on evidence of students' abilities. ECD consists of three components: claim, evidence, and task. The process of developing this assessment uses the research and development method by following the ADDIE stages: analysis, design, development, implementation, and evaluation. Data were collected through interviews with physics teachers, analyzing teachers documents, validating the assessment, and conducting task trials. The trials were conducted in two stages: one-to-one trials with one student and small-scale trials with 10 students. The analysis techniques included calculating validity using the Aiken Index, descriptive analysis of student responses in the one-to-one trial, and small-scale trials. The competencies measured in the assessment are based on scientific practice, including using and developing representations, analyzing and interpreting data, explaining with evidence, and evaluating information. Each measured competency in the assessment consists of two essay tasks. The validation results show that the developed assessment has high validity with an average Aiken score of 0.97. Teachers can use this assessment as a reference through stages to develop assessments that evaluate the achievement of learning objectives